PENGARUH KEPERCAYAAN DAN KUALITAS LAYANAN TERHADAP PERILAKU KONSUMEN APLIKASI DANA GEN Z DI KOTA JAMBI - Rosada; Fusfita, Nurlia; Agusriandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of financial technology has increased the adoption of digital wallets as a cashless transaction medium, particularly among Generation Z, who are highly engaged with digital technology. However, the use of digital wallet services is influenced not only by technological convenience but also by users’ trust and the quality of services provided by platform operators. This study aims to analyze the effect of trust and service quality on the consumer behavior of Generation Z users of the Dana digital wallet application in Jambi City, both partially and simultaneously. This research employed a quantitative approach using a survey method through questionnaires distributed to 100 respondents aged 20–24 years who had experience using the Dana application. The sample was selected using purposive sampling techniques. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination with SPSS software. The results showed that trust had a positive and significant effect on consumer behavior and became the most dominant variable influencing the use of the Dana application. Service quality also had a positive and significant effect on consumer behavior. Simultaneously, trust and service quality significantly influenced consumer behavior among Dana users. The study concludes that trust and service quality are important factors in supporting the sustainable adoption of digital wallet applications among Generation Z consumers.Top of Form